Qualitative analysis of it reliability and security in local government financial reporting - Dailibas, Dailibas; Nasution, R; Chaerudin, Chaerudin; Harahap, Muhammad Nasim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The study aims to explore and analyze the reliability and security of information technology (IT) in local government financial reporting in Indonesia. IT reliability and security are important factors in financial management, as reliable and secure information supports decision-making, attracts investment and builds public trust. However, threats to IT reliability and security can lead to negative consequences, such as data inaccuracies or the risk of information leakage. This research uses a qualitative approach with case studies on two local governments that have adopted IT in the financial reporting process. Data were obtained through in-depth interviews, observations and document reviews. The analysis focused on the impact of IT reliability and security on financial administration performance. The results show that improving IT reliability and security has a significant positive impact on local government financial management. Concrete impacts include increased public trust, operational efficiency and financial accountability. IT system reliability enables fast and accurate data processing, while IT security protects sensitive information from cyber threats. This research makes an important contribution by supporting previous research and expanding the discussion on the relationship between IT security and public trust, which has previously been less explored. The practical implications include recommendations for strengthening regulations and budget allocations for better IT infrastructure, as well as guidance on effective IT implementation strategies. The findings confirm that IT reliability and security are key elements in building a transparent and efficient local government administration system.